UPAYA UNITED NATIONS OFFICE ON DRUGS AND CRIMES DALAM MENANGANI PEREDARAN KOKAIN DI PERU (2001-2014) - Aziz, Raju Abdul; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Cocaine become one of the highest demand of illegal drugs in the world. Cocaine development began from Andean Mountain which include Argentina, Bolivia, Chile, Colombia, Ecuador, Peru, and Venezuela. The biggest market for this type of drugs are in East Europe, Latin America, and South East Asia. The people like buying cocaine because it is easy to consume. The consumer also does not need much time to feel the effect. Cocaine can destroy the human body such as lung, liver, brain tissue, and panchreas.This research uses International Organization theory of Umar S. Bakhri. Qualitative method and library research are applied in this research. The sources of information that used in this research are taken from book, journal, news, and internet.This research explains the efforts of UNODC as international organization to reduce cocaine’s development particulary in Peru. There are some hypothesis’ to describe the efforts which implemented by UNODC. This research also describes the development of cocaine growth year per year after the intervention from UNODC. The results of this research indicate that UNODC’s efforts can reduce the cocaine growth in Peru.Keywords: UNODC, cocaine, Peru, efforts, eradication